PERAN HAND TRAKTOR DALAM MENDUKUNG OPTIMALISASI LAHAN RAWA DI DESA TAPUS, KABUPATEN OGAN KOMERING ILIR: PERAN HAND TRAKTOR DALAM MENDUKUNG OPTIMALISASI LAHAN RAWA - Saleh, Edward; Siti Syaharani, Nyayu; Ressy Angli Permatasari, Ressy; Veni Vera, Vicentia (Universitas Andalas, 2025)
The use of swampland faces various challenges, such as flooded soil conditions, high acidity levels, and limited access to agricultural facilities and infrastructure. One of the solutions to overcome these challenges is the modernization of agricultural tools and machinery (alsintan), especially the use of hand tractors as an efficient soil tillage tool and in accordance with the characteristics of swampland. Tapus Village is one of the administrative areas located in Pampangan District, Ogan Komering Ilir Regency, South Sumatra Province. Tapus Village already has agricultural tools and machinery in the form of hand tractors that are quite adequate, but their use is still not optimal. The purpose of this study is to determine the role and strategy in optimizing hand tractor agricultural tools and machinery to support the management of swampland (OPLA) in Ogan Komering Ilir Regency in a more optimal and sustainable manner. In this study, methods were used in the form of literature study, gap analysis, SWOT (Strength, Weakness, Opportunity, and Threat) analysis, conducting needs and opportunities studies (KKP) and conducting observations and deep interviews with resource persons using questionnaires. The results of the study show that the optimization strategy of Alsintan hand tractor to support OPLA in Tapus Village can be carried out through the empowerment of farmers through training, socialization, and education on the use and maintenance of hand tractors, increasing the capacity of special operators, utilizing Alsintan hand tractors that are available, increasing UPJA and Alsintan workshops in Tapus Village. It is hoped that the results of this research can support the sustainability of the implementation of the strategy so that it can be carried out efficiently and effectively.